EDUCATIONAL IMPLEMENTATION AT MARGINALIZED SCHOLLS IN DENPASAR CITY - Suciani, Ni Made (E-Journal of Cultural Studies, 2014)
Some schools experienced termerjinalkan circumstances amid the bustle of the city of Denpasar . The problems studied are factors causing some schools experiencing marginalization , how to provide education to marginalized schools , and bagaimanaimplementasinya associated with the five pillars of national education policy and its implications for students , institutions, schools , and masyarakat.Penelitian inimenggunakan qualitative approach . The theory used is the deconstruction theory , structuration theory , and critical education theory . Data was collected using the method of observation , interviews , and documentary techniques , and analyzed qualitatively . The results showed that the appearance of marginalization at some schools due to cultural dualism between public schools and private schools , which includes the views and policies of the government , private sector and the impact of marginality teacher certification . Another factor is the culture , character and public perceptions of the school negeriserta labeling of the marginal private schools , and the lack of financial management and imaging schools to survive for the sake of prestige . In addition there are also technical factors such as the lack of human resource management , lack of competence danusaha - business competence improvement also poor communication and school partnerships with stakeholders , as well as the lack of supervision and evaluation of the achievement of national standards on school education pendidikan.Penyelenggaraan marginalized can be seen from intangible side as diseconomies kumunitas , dehumanization of education and culture in school imaging termarjinalkan.Sedangkan of the tangible results of self-evaluation is through education at school sekolah.Implementasi marginalized related to the five pillars of the national education policy is the availability , affordability , quality , equality and assuredness service besides it also analyzed the implications for students , schools and public institutions .
Keywords: provision of education; marginalized schools; and cultural dualism